An Analysis of Taboo Words in Blink 182’s Song Lyrics of “Enema of the State” Album - Suci Refika Wulan Sari (LINGUA LITERA : journal of english linguistics and literature, 2015)
This paper describes the findings of the study about taboo Words used in the Blink 182’s song lyrics. The rationale was that taboo words areforbidden to be used in speaking and writing, but have recently become the subject of a specialized publication as they frequently appear in somecontexts of speech, writing, speaking, and even in song. The objectives of the study were to find out what kinds of taboo words used in the Blink 182’s song lyrics and how often taboo words appear in the Blink 182’s song lyrics of Enema of the State album. descriptive qualitative method was used. All of the song lyrics in Enema of the State album (12 songs) were taken as the sample of the study. The data were then analyzed by using the procedures of data analysis by on aleong: transcription, election, classification, interpretation, and conclusion. The findings indicated that the total words in all the song lyrics in Enema of the State album were 2.520 words. It consisted of 33 taboo words and 2.487 non-taboo words. Of 12 songs, 3 songs used non-taboo words. There are Aliens Exist, Adam’s song, and Wendy Clear. These findings implied that taboo words starts gaining their popularity in songs.